Examination of nutrient content, dietary antioxidant capacity, dietary quality and dietary inflammatory load of some popular diet - Zengin, Fatmanur Hümeyra; Çevik, Aleyna (Scientific Web Journals (SWJ), 2024)
This study aimed to examine some popular diets' nutrient content, dietary antioxidant capacity, diet quality, and dietary inflammatory load. Materials and Method: Literature was reviewed to identify popular diets, and Atkins, vegan, Zone, Dukan, Mediterranean, alkaline, ketogenic, and Paleo diets were included in the study. Nutrient contents, antioxidant capacity, and oxygen radical absorbance capacity (ORAC) values of popular diets were determined using the Ebispro for Windows (BeBIS) program. Diet Quality Index-I (DQI-I) and Dietary Inflammatory Index were calculated. Results: When the antioxidant amounts of all dietary models were compared, the diet with the highest antioxidant content was the Paleo diet (6.0 mmol), and the lowest was the classic ketogenic diet (1.9 mmol). When the ORAC values of the dietary patterns were compared, the diet with the highest antioxidant capacity was the Paleo diet (23670), and the diet with the lowest antioxidant capacity was the Dukan cruise diet (1828). The diet with the lowest DII score was the vegan diet (-1.5), and the diet with the highest DII score was the classic ketogenic diet (5.9). According to the DII scores, vegan, Dukan, and Mediterranean diets have anti-inflammatory properties. Vegan diet had the highest DQI-I score (74). Zone (73) and Mediterranean (68) had the highest scoring diets. The diets with the lowest DQI-I scores were the Dukan (attack phase) (43) and the classic ketogenic diet (46). Conclusion: These findings provide valuable information on the nutritional adequacy of popular diets. Plant-based and balanced diets have better quality and nutrient profiles than low-carbohydrate diets.
Keywords: Nutrition and Dietetics (Other); Nutrition; Mediterranean diet; Ketogenic diet; Vegan diet; Beslenme ve Diyetetik (Diğer); Beslenme; Akdeniz diyeti; Ketojenik diyet; Vegan diyet; 2. Zero hunger; 3. Good health